El Salvador : Investment Climate Assessment, Volume 2, Detailed Findings and Recommendations - World Bank (Washington, DC, 2012)
This report identifies constraints to Salvadoran manufacturing firms, in the areas of governance and insecurity, physical infrastructure, access to finance and skills, quality and technology. The report uses a survey of manufacturing firms to benchmark El Salvador with respect to other countries of the region and the world, as well as to estimate the impact of investment climate constraints on firm performance. The report presents policy recommendations based on national and international data sources, the survey analysis and other Economic and Sector Work done by the Bank. In almost all investment climate indicators El Salvador performs substantially better than Honduras, Nicaragua and, to a lesser extent, Guatemala. The main exception is in the area of technology, where Guatemalan firms appear to be ahead of their Salvadoran counterparts. Despite these regional advantages, in global terms El Salvador faces important challenges associated with the need to enhance skills, and modernize the production technologies used by local manufacturers, increase the use of information and communication technologies, reduce the relatively high levels of insecurity, improve contract enforcement mechanisms, and decrease transportation and other logistic costs. Statistical analysis indicates that improvements in all four areas of the investment climate - governance and insecurity, infrastructure, finance and technology - have the potential to generate significant increases in firm productivity and exports. Even though the report includes a large number of detailed policy recommendations to improve the country's investment climate, two sets of policy measures deserve special attention: development and implementation of an Information and Communication Technology (ICT) strategy; and, creation of a high level entity responsible for the formulation, coordination, and evaluation of the country's policies to promote technology adoption and innovation.